Does work task motivation mediate the relationship between psychological capital and teacher well-being? - Zewude Girum Tareke; Hercz Maria (Psihologija, 2024)
This study examined the mediating role of work task motivation (WTM) in the relationship between psychological capital (PsyCap) and teacher well-being (TWB) in the higher educational context of Ethiopia. The Psychological Capital Questionnaire-12 (PCQ-12), Work Task Motivation Scale for Teachers (WTMST), and Teacher Well-Being Scale (TWBS) were used to collect and analyzed data from a sample of 596 university teachers employed at Ethiopia’s Amhara Regional State Universities. The results indicated that PsyCap had a direct and positive effect on WTM (β = 0.374, CI 95% [0.271, 474], p < .001) and TWB (β = 0.298, CI 95% [0.150, 0.430], p < .001). WTM also has a direct and positive impact on TWB (β = 0.472 CI 95% [.003, .481], p < .05). Besides, WTM fully mediated the relationship between PsyCap and TWB (β = 0.110, CI 95% [0.006, 0.206], p < 0.05). We also found that PsyCap intrinsic motivation identified regulation directly and positively, whereas external, introjected regulation, and amotivation negatively and directly predicted TWB. Finally, the dimensions of WT (intrinsic motivation, identified regulation, external regulation, and introjected regulation and amotivation)partially mediated the relationships between PsyCap and dimensions of TWB (workload, organizational, and student interaction well-being).